Lithium metal battery negative electrode framework material as well as preparation method and application thereof

By using a carbon shell combined with a molybdenum phosphide nanoparticle layer in lithium metal batteries, the lithium dendrites problem is solved, the directional deposition of lithium ions and the improvement of battery performance is achieved, the use of precious metals is avoided, and the battery is significantly improved stability and safety.

CN119297281APending Publication Date: 2025-01-10ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411311781.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The formation of lithium dendrites in lithium metal batteries leads to deterioration of battery performance and safety risks. The use of precious metal alloys in the prior art has problems of high cost and limited resources.

Method used

The carbon shell material is combined with the molybdenum phosphide nanoparticle layer, and the high potential characteristics of molybdenum phosphide guide the directional deposition of lithium ions inside the carbon shell to generate lithium phosphide as a solid electrolyte interface film, inhibit the formation of lithium dendrites, and pass Control the thickness ratio of the carbon shell to the molybdenum phosphide layer and the content of doped elements to ensure the stability of lithium deposition.

Benefits of technology

Effectively inhibit the generation of lithium dendrites, improve the energy density, cycle stability and safety performance of the battery, reduce production costs, and avoid the defects in the use of precious metals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297281A_ABST
    Figure CN119297281A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium metal battery negative electrode framework material and a preparation method and application thereof.The framework material comprises a carbon shell and a hollow inner cavity, a molybdenum phosphide nanoparticle layer is attached to the inner wall of the carbon shell, the carbon shell comprises secondary particles formed by agglomeration of primary particles, the particle size of the secondary particles of the carbon shell is larger than 200 nm, and the diameter of the molybdenum phosphide nanoparticle layer is smaller than that of the carbon shell. The ratio of the total thickness of the carbon shell and the molybdenum phosphide nanoparticle layer to the particle size of the secondary particles is lower than 1: 30, and the thickness ratio of the carbon shell to the molybdenum phosphide nanoparticle layer is 1: 2 or above. Due to the remarkable lithium deposition high potential characteristic of molybdenum phosphide, directional deposition of lithium ions in the spherical carbon shell is effectively promoted, in the process, molybdenum phosphide is reduced by lithium, lithium phosphide and elemental molybdenum with enhanced conductivity are generated, and ordered deposition of the lithium ions is further promoted. And the generated lithium phosphide effectively prevents the generation of lithium dendrites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy related technologies, and in particular to a lithium metal battery negative electrode skeleton material and a preparation method and application thereof. Background Art

[0002] In the context of rapid technological development, the improvement of lithium battery energy density has become a key technical obstacle to the performance leap of cutting-edge electronic products such as electric vehicles, drones, and smart phones. The core root of this challenge is that the capacity of traditional graphite negative electrode materials has approached its theoretical upper limit, which seriously limits the further improvement of the overall performance of the battery. Therefore, actively exploring and developing new negative electrode materials with higher capacity and better performance has become an urgent task to promote energy storage technology to overcome technical bottlenecks and achieve a revolutionary leap.

[0003] Among many new negative electrode materials, lithium metal negative electrode has a high theoretical specific capacity (up to 3860mAh / g) and a very low electrochemical potential (-3.04V vs.Li + / Li) has emerged as an ideal choice for improving the energy density of lithium batteries and extending the battery life of devices. However, the commercialization of lithium metal anodes faces severe challenges, mainly due to the problem of lithium dendrites that are easily formed during use. Lithium dendrites not only accelerate the degradation of battery performance, but may also pierce the diaphragm, causing internal short circuits and posing safety hazards, which seriously restricts its widespread application.

[0004] In order to deal with the problem of lithium dendrites, the scientific research community has proposed many innovative solutions. By precisely controlling the composition of the electrolyte, optimizing the performance of the diaphragm, and innovating the surface and structural design of the negative electrode materials, researchers have worked hard to inhibit the formation of lithium dendrites at the source. Among them, the use of lithium-philic materials to modify the surface of the negative electrode to reduce the deposition overpotential of lithium ions and increase the critical radius of lithium nucleation has become a highly anticipated research direction. This method can not only effectively inhibit the growth of lithium dendrites, but also significantly improve the performance stability and safety of the battery. In addition, the confined deposition strategy of lithium has also shown great potential. This strategy limits the deposition area of ​​lithium by cleverly designing the spatial structure, thereby effectively alleviating the stress concentration problem caused by volume change and further extending the service life of the battery. However, to achieve efficient deposition of lithium in a specific confined space, many technical challenges still need to be overcome. To this end, researchers are working on developing thin-shell carbon materials with internal lithium-philic modifications. This material can guide lithium ions to deposit evenly and stably inside the carbon shell by optimizing the synergistic effect of shell thickness and internal lithium-philic modification, fundamentally solving the problem of lithium dendrites and significantly improving the energy density, cycle stability and safety of lithium batteries. In the prior art, metals that can form alloys with lithium (such as precious metals such as gold, silver or magnesium, tin, etc.) are usually used as modified materials. Although it has certain advantages, it is costly and the potential of the alloy formed with lithium metal is slightly higher than the lithium equilibrium potential. The alloying potential is slightly higher than the lithium equilibrium potential, which is easily affected by electrochemical polarization, resulting in the deposition of lithium metal outside the carbon shell. For example, lithium-silver alloy is around 0.1V. Although it has certain advantages over lithium metal itself, the 100mV potential difference is easily smoothed by concentration polarization and electrochemical polarization, causing lithium metal to be deposited outside the carbon shell. In addition, precious metals also have many defects such as high cost and limited resources.

[0005] Therefore, developing a negative electrode skeleton material that can effectively inhibit lithium dendrites and avoid the shortcomings of metal elements is of great significance to promoting the commercialization of lithium metal battery technology. Summary of the invention

[0006] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a lithium metal battery negative electrode skeleton material, which can better inhibit lithium dendrites and better ensure that lithium is deposited inside the carbon shell.

[0007] According to one aspect of the present invention, a negative electrode skeleton material for a lithium metal battery is proposed, comprising a carbon shell and a hollow inner cavity, wherein a molybdenum phosphide nanoparticle layer is attached to the inner wall of the carbon shell, the carbon shell comprises secondary particles formed by agglomeration of primary particles, the particle size of the carbon shell secondary particles is greater than 200 nm, the ratio of the total thickness of the carbon shell and the molybdenum phosphide nanoparticle layer to the particle size of the secondary particles is less than 1:30, and the thickness ratio of the carbon shell to the molybdenum phosphide nanoparticle layer is above 1:2.

[0008] According to a preferred embodiment of the present invention, at least the following beneficial effects are achieved: a molybdenum phosphide nanoparticle layer is attached to the skeleton material of the present invention, and molybdenum phosphide effectively promotes the directional deposition of lithium ions inside the carbon shell due to its significant high potential characteristics of lithium deposition. In this process, molybdenum phosphide is not only reduced by lithium to generate lithium phosphide and molybdenum elements with enhanced conductivity, but also further promotes the orderly deposition of lithium ions. The generated lithium phosphide, as an excellent solid electrolyte interface film (SEI) modification layer, effectively prevents the formation of lithium dendrites and improves the safety performance of the battery. In addition, the skeleton material also shows effective inhibition of the volume expansion of the lithium metal negative electrode, and the cycle life of the lithium metal battery is extended by guiding the lithium metal to achieve directional deposition inside the carbon ball. Compared with the traditional lithium-philic layer, which mostly uses metals that can form alloys with lithium (such as magnesium, tin, etc., although including precious metals such as gold and silver, but the cost is high and the resources are limited), this solution ingeniously selects molybdenum phosphide, a high-potential negative electrode material, to modify the inner wall of the carbon shell. The lithium deposition potential of molybdenum phosphide is much higher than the equilibrium potential of lithium (specifically up to 1.6V vs.Li / Li + This significant difference ensures that lithium metal can be stably deposited inside the carbon shell rather than on the outside, thereby effectively avoiding the problem of uneven deposition caused by the small potential difference and the influence of concentration polarization and electrochemical polarization. In summary, the molybdenum phosphide nanoparticle layer design of the present invention has brought significant improvements to the energy density, stability, cycle life and safety performance of lithium metal batteries. The carbon shell covering the surface of the lithium-philic material is thinner, which is conducive to the deposition of lithium ions inside. The carbon shell covering the surface of the lithium-philic material is thinner, which is more conducive to the deposition of lithium ions inside.

[0009] In some embodiments of the present invention, the carbon shell is doped with N and / or S. Doping with N and / or S can reduce lithium deposition overcharge, and excessive doping affects the conductivity.

[0010] In some embodiments of the present invention, the doping amount of N and / or S in the carbon shell is 0.5-5%. The content of the doping elements is controlled within a suitable range to avoid affecting the conductivity.

[0011] In some embodiments of the present invention, the carbon shell includes secondary particles formed by agglomeration of primary particles.

[0012] In some embodiments of the present invention, the secondary particles are spherical or quasi-spherical.

[0013] In some embodiments of the present invention, the surface of the secondary particles contains a through-hole structure.

[0014] In some embodiments of the present invention, the secondary particles have a particle size of 300 to 3000 nm. Controlling the particle size within an appropriate range reduces the difficulty of manufacturing (avoiding the breakage of the pole piece or excessively harsh manufacturing conditions), and further increases the internal space for easy lithium deposition.

[0015] In some embodiments of the present invention, the secondary particles have a particle size of 500 to 900 nm.

[0016] In some embodiments of the present invention, the ratio of the total thickness of the carbon shell and the molybdenum phosphide nanoparticle layer to the particle size of the secondary particles is 1:8 to 22. The total shell thickness is controlled within this range, so that the shell volume ratio is within an appropriate range, which is more conducive to lithium deposition and can also better avoid lithium metal exposure.

[0017] In some embodiments of the present invention, the ratio of the total thickness of the carbon shell and the molybdenum phosphide nanoparticle layer to the particle size of the secondary particles is 1:12-18.

[0018] In some embodiments of the present invention, the ratio of the thickness of the carbon shell to the molybdenum phosphide nanoparticle layer is 1:2 to 11. Controlling the thickness of the carbon shell within this range can better control the lithium internal deposition overpotential and conductivity, which is more conducive to lithium internal deposition and shell formation.

[0019] In some embodiments of the present invention, the thickness ratio of the carbon shell to the molybdenum phosphide nanoparticle layer is 1:4-9.

[0020] In some embodiments of the present invention, the volume of the inner cavity accounts for 48.8% to 99.7% of the volume of the skeleton material. The material shell is thin as a whole, the cavity accounts for a large proportion, and the lithium deposition space is large.

[0021] According to another aspect of the present invention, a method for preparing the above-mentioned skeleton material is provided, comprising the following steps:

[0022] The aromatic compound and soluble molybdate are sequentially added to the phosphorus source solution, reacted, solid-liquid separated, solid phase collected, and calcined under an inert atmosphere to obtain the framework material, wherein the aromatic compound comprises at least one of an aromatic compound and a heteroaromatic compound.

[0023] According to a preferred embodiment of the preparation method of the present invention, at least the following beneficial effects are achieved: the preparation method of the present invention is easy to operate, requiring only one-step calcination, the lithium-philic layer and the carbon spheres themselves are formed at one time, no plating step is required, and the synthesis steps are simple. Furthermore, the soluble molybdate has an obvious price advantage over precious metals, and can also significantly reduce production costs.

[0024] In some embodiments of the present invention, the inert atmosphere includes an inert gas atmosphere or a nitrogen atmosphere.

[0025] In some embodiments of the present invention, the calcination temperature is 700-800°C.

[0026] In some embodiments of the present invention, during the calcination, the holding time is 1.5 to 2.5 hours.

[0027] In some embodiments of the present invention, before the calcination, the temperature is raised to the calcination temperature at a heating rate of 1 to 5° C. / min.

[0028] In some embodiments of the present invention, the heteroaryl compound is a heteroaryl compound containing N or S. The heteroaryl compound containing N or S can better combine with the hydroxyl group in tetrakishydroxymethylphosphonium chloride during the preparation process, thereby forming a supporting structure as a component in the self-assembled hollow sphere, and serving as a carbon source and reducing agent during carbonization, thereby having conductivity while avoiding the generation of high-valent molybdenum.

[0029] In some embodiments of the present invention, the N- or S-containing heteroaryl compound is selected from at least one of aniline, pyridine, and thiophene.

[0030] In some embodiments of the present invention, the soluble molybdate is selected from at least one of ammonium molybdate, alkali metal molybdate or magnesium molybdate. By controlling the solute concentration, shells of different particle sizes can be obtained.

[0031] In some embodiments of the present invention, the molar ratio of phosphorus to heteroaryl compound in the phosphorus source is 1.3-0.7: 1. The thickness ratio of the molybdenum phosphide nanoparticle layer to the carbon layer is adjusted by controlling the ratio of tetrakishydroxymethylphosphonium chloride to aniline.

[0032] In some embodiments of the present invention, the reaction time is 12-16 hours. The ratio between the overall shell thickness and the particle size is regulated by the synthesis time.

[0033] According to another aspect of the present invention, a negative electrode plate for a lithium metal battery is provided, comprising a negative electrode active material, wherein the negative electrode active material is the above-mentioned skeleton material.

[0034] According to a preferred embodiment of the lithium metal battery negative electrode plate of the present invention, there are at least the following beneficial effects: nitrogen-doped thin-shell hollow carbon spheres wrapped with lithium-philic material molybdenum phosphide are selected as lithium deposition skeletons, and the skeleton material is coated on the surface of the current collector as a lithium metal negative electrode plate as a negative electrode active material, and the volume change of the lithium metal negative electrode is suppressed by the method of conducting the directional deposition of lithium metal inside the carbon spheres, thereby extending the cycle life of the metal battery.

[0035] In some embodiments of the present invention, the negative electrode plate further includes a current collector, and the negative electrode active material is attached to the current collector.

[0036] In some embodiments of the present invention, a conductive agent and a binder are also attached to the surface of the current collector.

[0037] According to another aspect of the present invention, a lithium metal battery is provided, comprising the above-mentioned negative electrode plate.

[0038] According to the application of a preferred embodiment of the present invention, there are at least the following beneficial effects: the negative electrode sheet and lithium metal battery made of the negative electrode skeleton material of the present invention have multiple advantages such as good stability, long cycle life and high safety performance.

[0039] According to another aspect of the present invention, an electrical device is provided, comprising the above-mentioned lithium metal battery.

[0040] In some embodiments of the present invention, the power-consuming device is at least one of an electric car, a drone, or a smart phone.

[0041] According to a preferred embodiment of the present invention, the power-consuming device has at least the following beneficial effects: the lithium metal battery of the present invention has excellent performance and good application prospects.

[0042] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0044] Figure 1 This is a transmission electron microscope (TEM) image of the carbon shell prepared in Example 1 of the present invention.

[0045] Figure 2 This is a scanning electron microscope (SEM) image of the carbon skeleton material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0046] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of them. Based on the embodiments of the present invention, other embodiments obtained by technicians in this field without creative work are all within the scope of protection of the present invention. The test methods used in the embodiments are conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can be reagents and materials obtained from commercial channels. Unless otherwise specified, the same parameter in each embodiment has the same value. The embodiments described below are exemplary and are only used to explain the present invention, and cannot be understood as limitations on the present invention.

[0047] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0048] The following Examples 2 to 17 are obtained by adjusting the raw material concentration based on Example 1.

[0049] Example 1

[0050] In this example, a negative electrode skeleton material for a lithium metal battery is prepared. The skeleton material is composed of a nitrogen-containing carbon shell with a hollow inner cavity and a molybdenum phosphide nanoparticle layer, and the molybdenum phosphide nanoparticle layer is attached to the inner wall of the carbon shell. The carbon shell is composed of secondary particles formed by agglomeration of primary particles. The particle size of the secondary particles is 650-750nm, and the shell thickness (total thickness of the carbon shell and the molybdenum phosphide nanoparticle layer) and the particle size ratio is 1:14-1:16. The ratio of the carbon shell to the molybdenum phosphide nanoparticle layer thickness is 1:6-1:7. The specific process is:

[0051] (1) Preparation of precursor: 500 μL of tetrakis(hydroxymethyl)phosphonium chloride was dropped into 20 mL of deionized water, and then 250 μL of aniline was slowly added with a syringe under vigorous stirring to produce a white precipitate, and then 0.35 g of ammonium molybdate hydrate was added, followed by stirring for 12 h to produce a blue precipitate; the blue precipitate was then centrifuged, thoroughly washed with ethanol deionized water, and dried at 100 °C for 10 h to finally obtain a carbon shell precursor.

[0052] (2) High-temperature calcination: The obtained blue precursor was pyrolyzed in a tube furnace at 760°C at a heating rate of 1°C / min and maintained in an argon atmosphere for 2 h to obtain internal lithium-philic thin-shell hollow carbon spheres, i.e., the negative electrode skeleton material of lithium metal batteries.

[0053] Example 2

[0054] In this example, a lithium metal battery negative electrode skeleton material is prepared, which differs from Example 1 in that the particle size of the carbon shell secondary particles is between 500-600 nm.

[0055] Example 3

[0056] In this example, a lithium metal battery negative electrode skeleton material is prepared, which differs from Example 1 in that the particle size of the carbon shell secondary particles is between 800-900 nm.

[0057] Example 4

[0058] In this example, a lithium metal battery negative electrode skeleton material is prepared, which differs from Example 1 in that the ratio of shell thickness (total thickness of carbon shell and molybdenum phosphide nanoparticle layer) to particle size is 1:12-1:13.

[0059] Example 5

[0060] In this example, a lithium metal battery negative electrode skeleton material is prepared, which differs from Example 1 in that the ratio of shell thickness (total thickness of carbon shell and molybdenum phosphide nanoparticle layer) to particle size is 1:17-1:18.

[0061] Example 6

[0062] This example prepares a lithium metal battery negative electrode skeleton material, which differs from Example 1 in that the thickness ratio of the carbon shell to the molybdenum phosphide nanoparticle layer is 1:4-1:5.

[0063] Example 7

[0064] This example prepares a lithium metal battery negative electrode skeleton material, which differs from Example 1 in that: the inner lithium-philic thin-shell hollow carbon sphere has a carbon shell and molybdenum phosphide nanoparticle layer thickness ratio of 1:8-1:9.

[0065] Example 8

[0066] In this example, a lithium metal battery negative electrode skeleton material is prepared, which differs from Example 1 in that the particle size of the carbon shell secondary particles is between 300-400 nm.

[0067] Example 9

[0068] In this example, a lithium metal battery negative electrode skeleton material is prepared, which differs from Example 1 in that the particle size of the carbon shell secondary particles is between 2500-3000 nm.

[0069] Example 10

[0070] This example prepares a lithium metal battery negative electrode skeleton material, which differs from Example 1 in that the ratio of shell thickness (total thickness of carbon shell and molybdenum phosphide nanoparticle layer) to particle size is 1:8-1:10.

[0071] Embodiment 11

[0072] In this example, a lithium metal battery negative electrode skeleton material is prepared, which differs from Example 1 in that the ratio of shell thickness (total thickness of carbon shell and molybdenum phosphide nanoparticle layer) to particle size is 1:20-1:22.

[0073] Example 12

[0074] This example prepares a lithium metal battery negative electrode skeleton material, which differs from Example 1 in that the thickness ratio of the carbon shell to the molybdenum phosphide nanoparticle layer is 1:2-1:3.

[0075] Embodiment 13

[0076] This example prepares a lithium metal battery negative electrode skeleton material, which differs from Example 1 in that the thickness ratio of the carbon shell to the molybdenum phosphide nanoparticle layer is 1:10-1:11.

[0077] Embodiment 14

[0078] In this example, a lithium metal battery negative electrode skeleton material is prepared, which differs from Example 1 in that the particle size of the carbon shell secondary particles is between 4500-5000 nm.

[0079] Embodiment 15

[0080] This example prepares a lithium metal battery negative electrode skeleton material, which differs from Example 1 in that the ratio of shell thickness (total thickness of carbon shell and molybdenum phosphide nanoparticle layer) to particle size is 1:2-1:3.

[0081] Example 16

[0082] This example prepares a lithium metal battery negative electrode skeleton material, which differs from Example 1 in that the thickness ratio of the carbon shell to the molybdenum phosphide nanoparticle layer is 1:15-1:20.

[0083] Embodiment 17

[0084] This example prepares a lithium metal battery negative electrode skeleton material, which differs from Example 1 in that the carbon shell is not doped with heteroatoms and the aniline in the preparation process is replaced by benzene.

[0085] Comparative Example 1

[0086] This example prepares a lithium metal battery negative electrode skeleton material, which differs from Example 1 in that it does not contain a molybdenum phosphide nanoparticle layer. No phosphorus source and soluble molybdenum salt are added during the preparation process.

[0087] Comparative Example 2

[0088] This example prepares a lithium metal battery negative electrode skeleton material, which differs from Example 1 in that the particle size of the carbon shell secondary particles is between 100-200 nm.

[0089] Comparative Example 3

[0090] In this example, a lithium metal battery negative electrode skeleton material is prepared, which differs from Example 1 in that the ratio of shell thickness (total thickness of carbon shell and molybdenum phosphide nanoparticle layer) to particle size is 1:30-1:35.

[0091] Comparative Example 4

[0092] This example prepares a lithium metal battery negative electrode skeleton material, which differs from Example 1 in that the thickness ratio of the carbon shell to the molybdenum phosphide nanoparticle layer is 2:1-1:1.

[0093] Comparative Example 5

[0094] In this example, a lithium metal battery negative electrode skeleton material is prepared, which is different from Example 1 in that the average particle size of the carbon shell secondary particles is 500nm, and 5nm thick silver particles are attached inside. The preparation method is prepared by referring to Kim et al. Tuning Lithiophilic Sites of Ag-Embedded N-Doped Carbon Hollow Spheres via Intentional Blocking Strategy for Ultrastable Li Metal Anode in Rechargeable Batteries. (doi: 10.1021 / acssuschemeng.2c05918).

[0095] Test example

[0096] The morphology and performance of the negative electrode skeleton materials of lithium metal batteries prepared in the above examples and comparative examples were characterized.

[0097] 1) Morphological characterization

[0098] The negative electrode skeleton materials of lithium metal batteries prepared in the above examples and comparative examples were characterized by transmission electron microscopy and scanning electron microscopy. The characterization results of Example 1 are as follows: Figures 1-2As shown in the figure, the carbon shell is composed of secondary particles formed by the agglomeration of primary particles, which are spherical or quasi-spherical, hollow inside and with a through-hole structure on the surface.

[0099] 2) Performance Testing

[0100] The negative electrode skeleton materials of lithium metal batteries prepared in the above examples and comparative examples were prepared into negative electrode sheets of lithium metal batteries according to conventional techniques. Specifically, the negative electrode sheets of lithium metal batteries were mixed with a binder (polyacrylic acid / styrene-butadiene latex (PAA / SBR)) and a conductive agent (carbon nanotubes CNT) and a solvent N-methylpyrrolidone (NMP) in conventional proportions to form a slurry, which was then coated on the surface of a copper current collector to prepare a negative electrode sheet of a lithium metal battery. The sheet was used as the positive electrode, the lithium sheet was used as the negative electrode, and a button cell was assembled using a commercial carbonate electrolyte.

[0101] The battery was tested for coulombic efficiency with a charge and discharge rate of 1 mA / cm 2 The current density is 3 mAh / cm 2 The positive electrode is charged and discharged for a cycle at a capacity of 1 mA / cm 2 The current density is 3 mAh / cm 2 Then charge at 1mA / cm 2 Current density, 1 mAh / cm 2 The capacity of the battery was charged and discharged for 100 cycles. The test was carried out at room temperature and the discharge cut-off voltage was 1.0 V. The stability of each anode was determined based on the number of complete cycles and coulomb efficiency.

[0102] The test results are shown in Table 1 below.

[0103] Table 1

[0104]

[0105]

[0106] As can be seen from Table 1, when the shell particle size, the ratio of shell thickness to particle size, and the ratio of carbon shell to molybdenum phosphide layer thickness change, the material cycle performance fluctuates to a certain extent, but is generally at a relatively good level, significantly better than the skeleton material using metal as a lithium-philic material. Further, when the ratio of the total thickness of the carbon shell and the molybdenum phosphide nanoparticle layer to the particle size of the secondary particles is between 1:12 and 18, and the ratio of the thickness of the carbon shell to the molybdenum phosphide nanoparticle layer is between 1:4 and 9, the performance of the skeleton material is even better. The comparison between Examples 1-7 and 8-17 shows that when the shell diameter, the shell thickness to particle size ratio, and the carbon shell to molybdenum phosphide layer thickness ratio are outside the preferred range or do not contain heteroatoms (N and / or S, etc.), the material cycle performance will be affected to a certain extent. Comparing the results of Example 1 with Comparative Example 1, it is found that molybdenum phosphide modification significantly improves the cycle stability of the material, which is due to the induction of molybdenum phosphide material on the directional deposition of lithium metal. It can be seen from Comparative Example 1 and Comparative Example 2 that when the secondary particle size is too small, the internal space is too small, lithium deposition is difficult, and the cycle performance is poor. Comparing Example 1 with Comparative Example 3, it can be seen that when the shell is too thin and fragile, lithium metal is exposed. Comparing Example 1 with Comparative Example 4, it can be seen that when the carbon shell is too thick, the overpotential of lithium internal deposition becomes larger, which is not conducive to lithium internal deposition. Comparing the results of Example 1 with Comparative Example 5, it is found that the skeleton material performance prepared by the hollow carbon spheres modified with inner lithium-philic thin-shell hollow carbon spheres modified with molybdenum phosphide in the embodiment of the present invention can obtain equivalent or even significantly improved electrochemical performance compared with the hollow carbon spheres modified with precious metals (silver, etc.), which is related to the higher deposition potential of molybdenum phosphide. The use of the scheme of the present invention can significantly reduce costs and overcome the problems of limited precious metal resources and inconvenient mining and utilization.

[0107] The embodiments of the present invention are described in detail above, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A lithium metal battery negative electrode skeleton material, characterized in that: It comprises a carbon shell and a hollow inner cavity, wherein a molybdenum phosphide nanoparticle layer is attached to the inner wall of the carbon shell, the carbon shell comprises secondary particles formed by agglomeration of primary particles, the particle size of the carbon shell secondary particles is greater than 200nm, the ratio of the total thickness of the carbon shell and the molybdenum phosphide nanoparticle layer to the particle size of the secondary particles is less than 1:30, and the thickness ratio of the carbon shell to the molybdenum phosphide nanoparticle layer is greater than 1:

2.

2. The negative electrode skeleton material of a lithium metal battery according to claim 1, characterized in that: The carbon shell is doped with N and / or S; preferably, the carbon shell is doped with 0.5-5% by mass of N and / or S.

3. The negative electrode skeleton material of a lithium metal battery according to claim 1, characterized in that: The particle size of the secondary particles is 300-3000 nm; preferably, the particle size of the secondary particles is 500-900 nm.

4. The negative electrode skeleton material of a lithium metal battery according to claim 1, characterized in that: The ratio of the total thickness of the carbon shell and the molybdenum phosphide nanoparticle layer to the particle size of the secondary particles is 1:8-22; and / or, the ratio of the thickness of the carbon shell and the molybdenum phosphide nanoparticle layer is 1:2-11; preferably, the ratio of the total thickness of the carbon shell and the molybdenum phosphide nanoparticle layer to the particle size of the secondary particles is 1:12-18; and / or, the ratio of the thickness of the carbon shell and the molybdenum phosphide nanoparticle layer is 1:4-9.

5. The negative electrode skeleton material of a lithium metal battery according to claim 1, characterized in that: The volume of the inner cavity accounts for 48.8% to 99.7% of the volume of the skeleton material.

6. A method for preparing a skeleton material according to any one of claims 1 or 5, characterized in that: The steps include: Adding aromatic compounds and soluble molybdates to a phosphorus source solution in sequence, reacting, separating the solid and the liquid, collecting the solid phase, and calcining under an inert atmosphere to obtain the framework material, wherein the aromatic compound includes at least one of an aromatic compound and a heteroaromatic compound.

7. The method for preparing the skeleton material according to claim 6, characterized in that: Include at least one of the following conditions: 1) The calcination temperature is 700-800° C.; 2) During the calcination, the holding time is 1.5 to 2.5 hours; 3) before the calcination, the temperature is raised to the calcination temperature at a rate of 1 to 5°C / min; 4) The heteroaryl compound is a heteroaryl compound containing N or S; preferably, the heteroaryl compound containing N or S is selected from at least one of aniline, pyridine and thiophene; 5) The soluble molybdate is selected from at least one of ammonium molybdate, alkali metal molybdate or magnesium molybdate; 6) The molar ratio of phosphorus to heteroaryl compound in the phosphorus source is: 1.3-0.7:1; 7) The reaction time is 12-16 hours.

8. A negative electrode plate for a lithium metal battery, characterized in that: The invention comprises a negative electrode active material, wherein the negative electrode active material is the skeleton material according to any one of claims 1 to 6.

9. A lithium metal battery, characterized in that: Comprising the negative electrode sheet as described in claim 8.

10. An electrical device, characterized in that: Comprising the lithium metal battery as described in claim 9.